RASIO FUNDAMENTAL TERHADAP PERTUMBUHAN LABA: VARIABEL MODERASI UKURAN PERUSAHAAN (Fundamental ratio on income growth: Variables of company size moderation) - Andri Gunawan Putra As'ari; Tri Kartika Pertiwi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
To find out the performance of a company it is necessary to have a financial analysis, where in analyzing the financial statements will get a view of the good and bad financial performance. For this reason, this study aims to analyze the effect of the Liquidity Ratio, Solvency Ratio, Profitability Ratio, and Activity Ratio on profit growth with company size as a moderating variable. The population in this study was all trade retail companies that listed in Indonesia Stock Exchange in the period 2015-2018. The research samples was determined by using purposive sampling technique, so that obtained 21 trade retail companies that quality as the sample. The analysis technique used is moderation regression analysis. Based on the research result showed that Solvability, Profitability and Activity ratios has an effect on profit growth and company size is a moderation variabel. Liquidity Ratio has no effect on profit growth and company size not a moderating variable between Liquidity on profit growth.